Fire From The Standpoint Of Mythology And Culture Of Different Nations (Open Herald: Periodical of Methodical Research, 2026)
Fire is one of the most ancient symbolic concepts in human thought, which manifests itself as one of the main signs of holiness, change and existence in various religious systems. This article deals with the study of the essence of fire in the mythology and culture of nations who inhabited in Central Asia and ancient Great Britain. Furthermore, the role of fire in antique mythology of Greek is also studied in the article. Based on the analysis, it can be seen that fire holds dual nature